2010
DOI: 10.4067/s0717-97072010000100021
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Compatibility of Polymers in Common Solvent

Abstract: Polymers are considered as versatile material having number of applications. However, their properties depend upon the structure, molecular mass and its distribution and the interactions among polymer-polymer and polymer-solvent molecules. Hence it is necessary to synthesize a polymer with required specification, which is a difficult, time consuming and costly process. A highly successful alternative is to blend/ mix the existing polymers for the purpose. This process needs detail knowledge about the interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Blend will be considered compatible if the polymer is completely soluble in bitumen [31].Unification during storage period of blend is compatibility of mix [32]. Study found that compatibility of polymer modified bitumen is influenced by temperature and thermal properties of blend [33].A large number of polymers are not soluble in bitumen at some extent, separation occurs due to lose bonding between them [31]. To reduce the risk of separation among the mixture (blends) appropriate selection of either bitumen or polymer is important [32 and 33].…”
Section: Selection Of Waste Polymermentioning
confidence: 99%
“…Blend will be considered compatible if the polymer is completely soluble in bitumen [31].Unification during storage period of blend is compatibility of mix [32]. Study found that compatibility of polymer modified bitumen is influenced by temperature and thermal properties of blend [33].A large number of polymers are not soluble in bitumen at some extent, separation occurs due to lose bonding between them [31]. To reduce the risk of separation among the mixture (blends) appropriate selection of either bitumen or polymer is important [32 and 33].…”
Section: Selection Of Waste Polymermentioning
confidence: 99%
“…Some of these are mechanical mixing, i.e., extrusion [ 3 , 4 , 5 ]; injection molding [ 6 , 7 ]; roller milling, in which the polymers are mixed using heated rollers that can shear and blend the materials together; and solution mixing, in which the polymers are dissolved in a common solvent and then blended together [ 8 , 9 , 10 ]. It can be used in the pharmaceutical industry, in the plastics industry [ 11 , 12 ], in the textile industry, and elsewhere [ 13 , 14 , 15 ]. In addition, in situ polymerization is often used to obtain a material with improved properties [ 11 , 12 ], as well as reactive blending, in which chemical reactions between the polymers take place during the mixing process [ 16 , 17 , 18 ], and other processes in which different mixing methods are combined to obtain acceptable results.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, contradictory results can be found in the literature for certain systems [16]. With the ever-growing computational power and resource, molecular simulations have played an important role in materials modeling and subsequent technology development, which can provide valuable microscopic and mesoscopic insights into the phase morphology and the interfacial behaviors of the immiscible molecules [17,18]. In this study, molecular dynamics (MD) and mesoscopic dynamics (MesoDyn) simulations have been performed on PAN/PVP polymer blends to investigate their miscibility/immiscibility and mesoscopic morphologies In general, well-aligned, one-dimensional nanostructures exhibit much more excellent properties compared to their disordered counterparts [19].…”
Section: Introduction mentioning
confidence: 99%